Analisis Faktor Sanitasi Lingkungan yang Berhubungan dengan Kejadian Diare - Sumadi, Alan; Sari Murni, Nani; Wahyudi, Arie; Harokan, Ali (Avicenna: Jurnal Ilmiah, 2025)
Background: Data from the South Sumatra Provincial Health Office in 2022 showed that the incidence of diarrhea per 1,000 population of all ages was 270 cases. The impact of low sanitation coverage is a decrease in the quality of the living environment, contamination of drinking water sources, and an increase in the transmission of environmental-based diseases such as diarrhea. Metodh:This study aims to analyze environmental sanitation factors related to diarrhea in Pulau Geronggang Village, Pedamaran Timur District, Ogan Komering Ilir Regency in 2024. This study is quantitative with a cross-sectional design, the population of this study is all families living in Pulau Geronggang Village, Pedamaran Timur District, namely 309 families, a sample of 174 respondents. The sampling technique is purposive sampling. Data analysis is univariate, bivariate, and multivariate tests. Result:the statistical test analysis using the Chi-Square statistical test and multiple logistic regression where the results showed a significant relationship between age (0.001), socio-economic (0.010), knowledge (0.000), availability of clean water (0.010), behavior (0.000), and type of toilet (0.010). There is no relationship between gender (0.167), quality of clean water (0.167), availability of toilets (0.167), waste management (0.410), and availability of SPAL (0.605). From the results of the multivariate statistical test, the dominant factor in the incidence of diarrhea is behavior (p = 0.000; OR = 13.086).Conclussion: It is expected that the relevant government can add programs and develop regional progress, especially in the Pedamaran Timur sub-district, both to improve health and economic and socio-cultural standards and the availability of clean water for the community in the area Keywords : diarrhea, determinants, environmental sanitation